Diet-induced adaptive thermogenesis requires neuropeptide FF receptor-2 signalling. Issue 1 (December 2018) - Zhang, Lei; Ip, Chi; Lee, I-Chieh; Qi, Yue; Reed, Felicia; Karl, Tim; Low, Jac; Enriquez, Ronaldo F.; Lee, Nicola; Baldock, Paul; Herzog, Herbert
Abstract Excess caloric intake results in increased fat accumulation and an increase in energy expenditure via diet-induced adaptive thermogenesis; however, the underlying mechanisms controlling these processes are unclear. Here we identify the neuropeptide FF receptor-2 (NPFFR2) as a critical regulator of diet-induced thermogenesis and bone homoeostasis.Npffr2 −/− mice exhibit a stronger bone phenotype and when fed a HFD display exacerbated obesity associated with a failure in activating brown adipose tissue (BAT) thermogenic response to energy excess, whereas the activation of cold-induced BAT thermogenesis is unaffected. NPFFR2 signalling is required to maintain basal arcuate nucleus NPY mRNA expression. Lack of NPFFR2 signalling leads to a decrease in BAT thermogenesis under HFD conditions with significantly lower UCP-1 and PGC-1α levels in the BAT. Together, these data demonstrate that NPFFR2 signalling promotes diet-induced thermogenesis via a novel hypothalamic NPY-dependent circuitry thereby coupling energy homoeostasis with energy partitioning to adipose and bone tissue. Excess caloric intake leads to increased thermogenesis in brown adipose tissue, to limit weight gain. Here, the authors show that neuropeptide FF receptor-2 signalling promotes thermogenesis via control of NPY expression in the arcuate nucleus, and that it absence in mice leads to a failure of activation of diet-induced thermogenesis and the development of exacerbated obesity.